2020
DOI: 10.1016/j.jeurceramsoc.2019.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization behavior and IR structure of yttrium aluminosilicate glasses

Abstract: The crystallization of four Y 2 O 3-Al 2 O 3-SiO 2 (YAS) glasses were investigated to prepare YAS glass ceramics precipitated singly/mainly Y 2 Si 2 O 7 or Y 4.67 (SiO 4) 3 O apatite, and to explore the crystallization difference between the stoichiometric parent glass (SPG) and non-stoichiometric parent glass (NSPG). The DSC results revealed that glass locating at the higher liquidus surface temperature has lower crystallization peak temperature, which indicating that the corresponding glass has higher crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 32 publications
3
4
0
Order By: Relevance
“…In the Raman spectra, it is also noticed that the band at 1120 cm −1 is only present in the AK-0Y and AK-3Y glasses, disappearing when the Y 2 O 3 composition is 5% and 12% (glasses AK-5Y and AK-12Y). This observation is attributed to the disappearance of the SiO 4 units to form new NBOs that, together with the shift of the band centered at 1000 cm −1 towards lower frequencies and it increases in intensity as the Y 2 O 3 concentration increases, corroborates the effect of Y 2 O 3 as a network modifier at the highest concentrations and the formation of large amounts of NBO [34].…”
Section: Glass Characterizationsupporting
confidence: 55%
See 1 more Smart Citation
“…In the Raman spectra, it is also noticed that the band at 1120 cm −1 is only present in the AK-0Y and AK-3Y glasses, disappearing when the Y 2 O 3 composition is 5% and 12% (glasses AK-5Y and AK-12Y). This observation is attributed to the disappearance of the SiO 4 units to form new NBOs that, together with the shift of the band centered at 1000 cm −1 towards lower frequencies and it increases in intensity as the Y 2 O 3 concentration increases, corroborates the effect of Y 2 O 3 as a network modifier at the highest concentrations and the formation of large amounts of NBO [34].…”
Section: Glass Characterizationsupporting
confidence: 55%
“…Depending on the composition, there are additional medium-intensity bands centered around 1120 cm −1 , 750 cm −1 , and 360 cm −1 , as well as three small bands or shoulders at 1180 cm−1, 680 cm −1 , and 610 cm −1 . The wide bands located at 980 and 1120 cm −1 are assigned to the Si-O-X bonds with X = Al, Y, Zr, Sn [31][32][33][34] and to the presence of Q n units (n = 0, 1, 2, 3, 4) where Q represents the SiO 4 tetrahedra and n the number of bridging oxygens (BOs). These Q n units are formed after the BOs are broken by network modifier elements (Na, K, Ca, etc.)…”
Section: Glass Characterizationmentioning
confidence: 99%
“…As the heat-treatment temperature increased, the band in the NCFs shifted from 936 to 951 cm –1 . This slight redshift was explained by a decrease in the Q 1 species, which implied that more terminal oxygen atoms were embedded in the nanocrystals. , Moreover, a sharp small peak at 1258 cm –1 appeared in the Raman spectrum of NCF2. With an increase in the annealing temperature, the peak became increasingly obvious in NCF3 and NCF4.…”
Section: Resultsmentioning
confidence: 99%
“…The annealing temperature of doped HfO 2 film is high, which can be attributed to the crystallization temperature of La 2 O 3 , SiO 2 , Al 2 O 3 and Y 2 O 3 being higher than that of ZrO 2 . [35][36][37][38][39][40] In addition, it was observed that the 2P r value of HZO film exhibited large fluctuations with increase in annealing temperature, suggesting that a difference in the volume fraction of the ferroelectric o-phase occurs. It is clear that the crystallization temperatures of our HZO film are reflected in a lower annealing temperature of 400 • C while maintaining a superior 2P r value of 54.6 µC•cm −2 .…”
Section: Resultsmentioning
confidence: 99%